Unprecedented Dual Role of Polyaniline for Enhanced Pseudocapacitance of Cobalt–Iron Layered Double Hydroxide. Issue 7 (9th February 2022) - Mahmood, Azhar; Zhao, Bolin; Javed, Muhammad Sufyan; He, Dequan; Cheong, Weng‐Chon; Han, Dongxue; Niu, Li
Abstract: Creating nanosized pores in layered materials can increase the abundant active surface area and boost potential applications of energy storage devices. Herein, a unique synthetic strategy based on polyaniline (PANI) doped 2D cobalt–iron layered double hydroxide (CoFe‐LDH/P) nanomaterials are designed, and the formation of pores at low temperature (80 °C) is developed. It is found that the optimized concentration of PANI creates the nanopores on the CoFe‐LDH nanosheets among all other polymers. The well‐ordered pores of CoFe‐LDH/P allow the high accessibility of the redox‐active sites and promote effective ion diffusion. The optimized CoFe‐LDH/P2 cathode reveals a specific capacitance 1686 (1096 Cg −1 ) and 1200 Fg −1 (720 Cg −1 ) at 1 and 30 Ag −1 respectively, a high rate capability (71.2%), and a long cycle life (98% over 10 000 cycles) for supercapacitor applications. Charge storage analysis suggests that the CoFe‐LDH/P2 electrode displays a capacitive‐type storage mechanism (69% capacitive at 1 mV s −1 ). Moreover, an asymmetric aqueous supercapacitor (CoFe‐LDH/P2//AC) is fabricated, delivering excellent energy density (75.9 Wh kg −1 at 1124 W kg −1 ) with outstanding stability (97.5%) over 10 000 cycles. This work opens a new avenue for designing porous 2D materials at low temperature for aqueous energy storage devices. Abstract : Polyaniline doped 2D cobalt–iron layered double hydroxides (CoFe‐LDHs) have a well‐defined 2D morphology, controllable nanopores, high specific surface area, and exhibit superior specific high pseudocapacitive charge storage.